Late offspring effects of antenatal thyroid screening. Issue 1 (23rd July 2022) - Panagiotou, Grigorios; Taylor, Peter N; Rees, D Aled; Okosieme, Onyebuchi E
Abstract: Background: Thyroid dysfunction in pregnancy is associated with adverse offspring outcomes and recent birth-cohort studies suggest that even mild degrees of thyroid dysfunction may be linked with a range of late cognitive and behavioural effects in childhood and adolescence. Sources of data: This review summarizes recent literature of observational studies and critically appraises randomized controlled trials (RCTs) of antenatal thyroid screening and Levothyroxine intervention. Areas of agreement: Overt hypothyroidism and hyperthyroidism carry significant risks for unfavourable offspring outcomes and should be appropriately corrected in pregnancy. Areas of controversy: The significance of subclinical hypothyroidism and hypothyroxinaemia is still unclear. Meta-analyses of birth-cohort studies show associations of maternal subclinical hypothyroidism and hypothyroxinaemia with intellectual deficits, attention deficit hyperactivity disorder (ADHD) and autism spectrum disorders, while hyperthyroidism and high-normal FT4 were linked with ADHD. RCTs have shown no benefits of screening on neurodevelopmental outcomes although Levothyroxine could have been initiated too late in pregnancy in these trials. Growing points: A small number of studies have shown inconsistent associations of maternal thyroid dysfunction with offspring cardiometabolic indices including blood pressure and body weight. Correction of maternal thyroid dysfunction was, however, associated with favourable long-term metabolic profiles in mothers, including lipid profiles, fat mass and body mass index. Antenatal thyroid screening may therefore present opportunities for optimizing a wider range of outcomes than envisaged. Areas for developing research: Future trials with early antenatal thyroid screening and intervention are necessary to clarify the impact of screening on late offspring and maternal effects.